1997
DOI: 10.1071/wr96080
|View full text |Cite
|
Sign up to set email alerts
|

Initial Changes in the Avian Communities of Remnant Eucalypt Woodlands following a Reduction in the Abundance of Noisy Miners, Manorina melanocephala

Abstract: It has been postulated that aggressive honeyeaters like the noisy miner, Manorina melanocephala, may contribute to rural tree decline by excluding small insectivorous birds from remnant patches of woodland, thereby reducing the level of predation upon defoliating insects. Previous studies provide correlational evidence that avian diversity and abundance is lower in remnant patches of woodland occupied by noisy miners than in those without noisy miners. Noisy miners were removed from three small remnant patches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 14 publications
9
123
4
Order By: Relevance
“…[51] [60] [61], as well as data from studies on despotic avian species e.g. [26]- [28], have shown similar effects for canopy arthropods. Our results also showed that the assemblage of the insect canopy community was not significantly affected by bell miner presence.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[51] [60] [61], as well as data from studies on despotic avian species e.g. [26]- [28], have shown similar effects for canopy arthropods. Our results also showed that the assemblage of the insect canopy community was not significantly affected by bell miner presence.…”
Section: Discussionmentioning
confidence: 98%
“…[22]- [25], or a reduction of insectivorous birds and the increase of a despotic species results in an indirect increase in damaging herbivorous insects e.g. [14] [26]- [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are interspecific factors. The presence of aggressive honeyeaters, particularly the Noisy Miner (Manorina melanocephala) has been shown to be a significant determinant of the bird community in southeastern Australia (Grey et al 1997(Grey et al , 1998Ford et al 2001). Changing landscape structure can alter species interactions (Schmiegelow and Monkkonen 2002), which could affect species distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Within a farming unit, the sites that have been the targets of ecological restoration include arable land for fallow or undersowing, areas adjacent to sensitive urban areas such as schools and roads, farm woodland, field margins including uncultivated areas (set aside), headlands and hedges, grassland, land surrounding aquifers and land water catchments, mid-field strips (beetle banks and cover strips), roadside verges, scrub, waterways and riparian areas ( Thomas et al 1991;Fortin & Arnold 1997;Grey et al 1997;Brickle et al 2000;Wickramasinghe et al 2003;Bowie & Frampton 2004;Bro et al 2004;Carvell et al 2004;MacLeod et al 2004;Pywell et al 2004;Pywell et al 2005a,b;Bowie et al 2006). The paper by Ryan et al (2002) is a good example of how land attributes such as aspect, elevation, soil depth and slope can be used in farmscale site selection for farm forestry.…”
Section: Where Does Ecological Restoration Take Place?mentioning
confidence: 99%